1994
DOI: 10.1002/ajim.4700260210
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cancer morbidity of finnish chlorophenoxy herbicide applicators: An 18‐year prospective follow‐up

Abstract: An 18-year follow-up for mortality and cancer morbidity was conducted in a cohort of 1,909 men who had started spraying chlorophenoxy herbicides (mixture of 2,4-dichlorophenoxyacetic acid [2,4-D] and 2,4,5-trichlorophenoxyacetic acid [2,4,5-T]) in 1955 through 1971. In all, 384 persons had died during the follow-up, and there was a slight deficit in natural deaths (standardized mortality ratio [SMR] 0.84; 95% confidence interval [CI] 0.75-0.94). By contrast, there was a small, nonsignificant increase in accide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…NHL or malignant lymphoma risk was linked to phenoxyacetic acid herbicides, in several studies (9, 10, 15) but not in others (11,(16)(17)(18). Cohorts of workers who manufacture 2,4-D and other phenoxy herbicides have not shown statistically significant excesses of NHL (19)(20)(21), but most were small cohorts that lacked sufficient power to detect moderate increases in risk (22).…”
Section: Discussionmentioning
confidence: 99%
“…NHL or malignant lymphoma risk was linked to phenoxyacetic acid herbicides, in several studies (9, 10, 15) but not in others (11,(16)(17)(18). Cohorts of workers who manufacture 2,4-D and other phenoxy herbicides have not shown statistically significant excesses of NHL (19)(20)(21), but most were small cohorts that lacked sufficient power to detect moderate increases in risk (22).…”
Section: Discussionmentioning
confidence: 99%
“…Relative risk estimates for other categories of exposure duration (one year or more) ranged between 0.66 and 1.21. In a Finnish cohort of employers involved in chemical brushwood control, Asp et al 76 reported an inverse association with chlorophenoxy herbicides (SMR 5 0.35, 95% CI: 0.01-1.97).…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%
“…The strongest association links non-Hodgkin's lymphoma and 2, 4-D, phenoxyacetic acid herbicide (10). Other studies have not shown the association to be consistent (7,81). Several meta-analyses of cancers in agricultural associations have shown increased risk for lip cancer and multiple myeloma (1, 15, 48, 120).…”
Section: Pesticide Exposurementioning
confidence: 99%